(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2010)
The reaction of 1-R-2-ме-1H-imidazo[2,1-a]isoindole with maleinimide derivatives at reagents ratio 1:2 was investigated. New derivatives of rearranged adducts of Michael-Diels-Alder were synthesised under thermodynamic control conditions.